Comparison of brittle star (Echinoderm: Ophiuroidea) diversity and species composition between two substrates in the intertidal zone - SYIFA MAULIDIA; TRI ATMOWIDI; ISMILIANA WIRAWATI; WINDRA PRIAWANDIPUTRA (Society for Indonesian Biodiversity, 2025)
Abstract. Maulidia S, Atmowidi T, Wirawati I, Priawandiputra W. 2025. Comparison of brittle star (Echinoderm: Ophiuroidea) diversity and species composition between two substrates in the intertidal zone. Biodiversitas 26: 2189-2197. Brittle stars are essential species in marine ecosystems. These macrozoobenthic organisms help clean the sea of organic particles and serve as food for demersal fish. However, further research on brittle stars in the intertidal zone of West Java, Indonesia is needed, particularly on two different substrates: seagrass and coral. This study examined the diversity and composition of brittle stars in the intertidal zone of West Java at Ujung Genteng Beach, Sancang Beach, and Pangandaran Beach. The quadrant transect method was used for sampling, with 30 plots at each station on each beach. Each plot measured 2×2 m, with a distance of at least 2 m between plots. We identified 12 species of brittle stars. Ophiocoma erinaceus and O. scolopendrina were found at all sampling locations, with O. scolopendrina is the highest abundance. A species previously unreported in Indonesia, O. anaglyptica, was found on coral substrates, and Ophiactis savignyi, a fissiparous brittle star that reproduces asexually, was found at Pangandaran on seagrass substrates. Pangandaran Beach exhibited the highest diversity (H': 1.4), with corals being the most important substrate for brittle star habitat. In contrast, the highest Evenness Index was found at Sancang Beach with seagrass substrates (E: 0.89). This indicates that brittle stars are most abundant at Pangandaran Beach but were more evenly distributed at Sancang Beach.